2005
DOI: 10.1111/j.1540-8175.2005.04056.x
|View full text |Cite
|
Sign up to set email alerts
|

Caseous Calcification of the Mitral Annulus: Unusual Case of Spontaneous Resolution

Abstract: Mitral annular calcification (MAC) is a common echocardiographic finding. Caseous calcification is a rare variant appearing as a round, tumor-like mass with central echolucent area located in the periannular region. Although occasionally misdiagnosed as a tumor and submitted to exploratory cardiotomy, this lesion appears to carry a benign prognosis. The true significance of caseous calcification is unknown; it might be an early and reversible stage of MAC or an atheroma-like lesion. We describe a case of caseo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 14 publications
1
26
1
4
Order By: Relevance
“…There are only 5 cases reported in the literature where heart surgery was performed due to CCMA-induced severe mitral regurgitation and HF [5,6]. There are data that CCMA may have a regressive or progressive nature [1,10], but in the literature, we have found no data of such a rapid progression and deterioration in the clinical course, as it happened in our case.…”
Section: Discussioncontrasting
confidence: 50%
“…There are only 5 cases reported in the literature where heart surgery was performed due to CCMA-induced severe mitral regurgitation and HF [5,6]. There are data that CCMA may have a regressive or progressive nature [1,10], but in the literature, we have found no data of such a rapid progression and deterioration in the clinical course, as it happened in our case.…”
Section: Discussioncontrasting
confidence: 50%
“…Most of the patients were asymptomatic or presented with dyspnea, probably unrelated to the mass. In one patient there was a spontaneous dissolution [18]. One patient had a mitral valve stenosis and another had progressive severe mitral valve regurgitation.…”
Section: Discussionmentioning
confidence: 97%
“…[13][14][15][16][17][18][19]. Alkadhi, et al [17] reported on 64-slice MDCT imaging of a similar mass with peripheral calcification and central hyperdensity.…”
Section: Discussionmentioning
confidence: 98%
“…According to some authors, absence of treatment seems to be a good option in the absence of clinical manifestations [1,2]. Cases of retransformation of CCMA into CMA have been reported [1,2] and even cases of spontaneous resolution [6]. However, hemodynamic problems and strokes are an indication for curative surgery or for preventing recurrence.…”
Section: Discussionmentioning
confidence: 97%